Recent Progress in Sub-Bottom Profiling— The SBP 120 Example. - Theuillon, Gwladys (The International Hydrographic Review, 2010)
Recent narrow beam sub bottom profilers achieve improved performances in terms of signal-to-noise ratio and resolution. Thus, the potential of these systems for detection of buried objects and also the inversion of sediment geo-acoustic parameters are high provided the device characteristics are correctly known. This note gives an overview of the results that can be obtained with a high resolution sub bottom profiler and stresses the importance of calibrating these systems when characterizing the geo-acoustic properties of sediments.